A gut microbiome signature for HIV and metabolic dysfunction-associated steatotic liver disease - Martínez-Sanz, Javier; Talavera-Rodríguez, Alba; Díaz-Álvarez, Jorge; Rosas Cancio-Suárez, Marta; Rodríguez, Juan Miguel; Alba, Claudio; Montes, María Luisa; Martín-Mateos, Rosa; Burgos-Santamaría, Diego; Moreno, Santiago; Serrano-Villar, Sergio; Sánchez-Conde, Matilde (Frontiers in Immunology, 2023)
Introduction Metabolic dysfunction-associated steatotic liver disease (MASLD), has emerged as an increasingly recognized problem among people living with HIV (PLWH). The gut-liver axis is considered to be strongly implicated in the pathogenesis of MASLD. We aimed to characterize the gut microbiota composition in PLWH and MASLD and compare it with that of two control groups: PLWH without MASLD and individuals with MASLD without HIV infection. Methods We collected clinical data and stool samples from participants. Bacterial 16S rRNA genes were amplified, sequenced, and clustered into operational taxonomic unit. Alpha diversity was studied by Shannon and Simpson indexes. To study how different the gut microbiota composition is between the different groups, beta diversity estimation was evaluated by principal coordinate analysis (PCoA) using Bray-Curtis dissimilarity. To further analyze differences in microbiome composition we performed a linear discriminant analysis (LDA) effect size (LEfSe). Results We included 30 HIV+MASLD+, 30 HIV+MASLD- and 20 HIV-MASLD+ participants. Major butyrate producers, including Faecalibacterium, Ruminococcus, and Lachnospira dominated the microbiota in all three groups. Shannon’s and Simpson’s diversity metrics were higher among MASLD+ individuals (Kruskal-Wallis p = 0.047). Beta diversity analysis showed distinct clustering in MASLD-, with MASLD+ participants overlapping regardless of HIV status (ADONIS significance <0.001). MASLD was associated with increased homogeneity across individuals, in contrast to that observed in the HIV+NAFDL- group, in which the dispersion was higher (Permanova test, p value <0.001; ANOSIM, p value <0.001). MASLD but not HIV determined a different microbiota structure (HIV+MASLD- vs. HIV+MASLD+, q-value = 0.002; HIV-MASLD+ vs. HIV+MASLD+, q-value = 0.930; and HIV-MASLD+ vs. HIV+MASLD-, q-value < 0.001). The most abundant genera in MASLD- were Prevotella, Bacteroides, Dialister, Acidaminococcos, Alloprevotella, and Catenibacterium. In contrast, the most enriched genera in MASLD+ were Ruminococcus, Streptococcus, Holdemanella, Blautia, and Lactobacillus. Conclusions We found a microbiome signature linked to MASLD, which had a greater influence on the overall structure of the gut microbiota than HIV status alone.